Analysis of Land Cover Change Due to Urban Growth in Central Ternate District, Ternate City using Cellular Automata-Markov Chain - Philia Christi Latue; Heinrich Rakuasa (Journal of Applied Geospatial Information, 2023)
The increase in population and the increasing flow of urbanization in Central Ternate District make the need for land to live also increase as a result of which there will be inconsistencies or inequalities between land needs and available land, a decrease in environmental carrying capacity and environmental damage in the future. This study aims to analyze changes in land cover due to urban growth in Central Ternate District, Ternate City using The Automata- Markov Chain. Cellular Automata- Markov Chain is used to analyze and predict land cover changes in 2002, 2012, 2022 and 2031. The results showed that residential land will continue to experience an increase in area along with population growth and the high demand for land to settle. The results of this study are expected to be input in policy making related to the arrangement and utilization of space in The Central Ternate District in the future.